Gli epistolari cristiani dei primi cinque secoli e il trasformarsi delle lettere - Burini de Lorenzi, Clara (Augustinianum, 2016)
The immense wealth of Greek and Latin Christian epistolography shows that in the first five centuries, the type of the letter reflects particularly the numerous topics in which theological and doctrinal issues, ecclesial and liturgical matters, and moral and social developmental questions are addressed. The epistolary genre increasingly becomes richer and more diversified as each letter bears witness to the faith and culture of its author. The pedagogical purpose remains dominant while the contents reflect the many issues and problems that concern both the sender and receiver in matters of doctrine, the Church, and the reality of social life. The line of argument and style indicate at the same time the author’s culture and heritage as received from the classical tradition.